ECOGRAFIA E SUAS PLICAÇÕES NA OBSTETRÍCIA - Mauad Filho, Francisco; Molinari, Marcelo Braga; Ferreira, Adilson Cunha; Molinari, Rogério Braga; Molinari, Eduardo Braga (VITTALLE - Revista de Ciências da Saúde, 2017)
Ver no documento